DEEP LEARNING : ARAH BARU KURIKULUM PENDIDIKAN DI ERA GLOBALISASI - Rahmat; Syamsul Aripin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Education in the era of globalization faces significant challenges in preparing the younger generation to keep up with the rapid technological advancements, one of which is by utilizing the concept of Deep Learning. Deep Learning, which is a part of Artificial Intelligence (AI), has transformed many sectors, including education. This technology opens opportunities to improve the quality of learning through more adaptive and personalized systems. This article discusses how the implementation of Deep Learning can serve as a new direction in the development of educational curricula, as well as the challenges and opportunities faced by educational institutions in integrating this technology. By exploring the potential of Deep Learning, education in the era of globalization can be more effective in meeting the needs of learning that are more relevant and responsive to the changing times.